2005
DOI: 10.1128/jvi.79.19.12231-12241.2005
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Human Immunodeficiency Virus Type 1 Envelope Glycoprotein Fusion by a Membrane-Interactive Domain in the gp41 Cytoplasmic Tail

Abstract: Truncation of the human immunodeficiency virus (HIV) or simian immunodeficiency virus (SIV) gp41cytoplasmic tail (CT) can modulate the fusogenicity of the envelope glycoprotein (Env) on infected cells and virions. However, the CT domains involved and the underlying mechanism responsible for this "inside-out" regulation of Env function are unknown. HIV and SIV CTs are remarkably long and contain amphipathic alpha-helical domains (LLP1, LLP2, and LLP3) that likely interact with cellular membranes. Using a cell-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
112
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 117 publications
(118 citation statements)
references
References 100 publications
(107 reference statements)
5
112
1
Order By: Relevance
“…The HIV-1 gp41 CT consists of the "Kennedy" polypeptide sequence (aa 731-752) and the lentivirus lytic peptide (LLP1-2, aa 773-862), which contains three highly conserved ␣-helix domains as follows: LLP1 (aa 833-862), LLP2 (aa 773-793), and LLP3 (aa785-807) (11). The HIV-1 gp41 CT has many functions, including interaction with the plasma membrane, decrease of bilayer stability, alteration of membrane ionic permeability, and mediation of cell killing (10,(12)(13)(14)(15)(16). Recent studies have shown that the gp41 CTs of HIV and simian immunodeficiency virus correlate with their infectivity and Env-mediated cell-cell fusion (10,15).…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…The HIV-1 gp41 CT consists of the "Kennedy" polypeptide sequence (aa 731-752) and the lentivirus lytic peptide (LLP1-2, aa 773-862), which contains three highly conserved ␣-helix domains as follows: LLP1 (aa 833-862), LLP2 (aa 773-793), and LLP3 (aa785-807) (11). The HIV-1 gp41 CT has many functions, including interaction with the plasma membrane, decrease of bilayer stability, alteration of membrane ionic permeability, and mediation of cell killing (10,(12)(13)(14)(15)(16). Recent studies have shown that the gp41 CTs of HIV and simian immunodeficiency virus correlate with their infectivity and Env-mediated cell-cell fusion (10,15).…”
mentioning
confidence: 99%
“…The HIV-1 gp41 CT has many functions, including interaction with the plasma membrane, decrease of bilayer stability, alteration of membrane ionic permeability, and mediation of cell killing (10,(12)(13)(14)(15)(16). Recent studies have shown that the gp41 CTs of HIV and simian immunodeficiency virus correlate with their infectivity and Env-mediated cell-cell fusion (10,15). The mutations or truncations of gp41 CT can affect HIV-1 Env-mediated cell-cell fusion, presumably because of modulation of the fusogenicity of Env (17,18).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Using a cell-cell fusion assay and a panel of HIV Envs with stop codons at various positions in the CT, we showed that truncations of gp41 proximal to the most N-terminal alpha helix, LLP2 (lentivirus lytic peptide), increase fusion efficiency and expose CD4-induced epitopes in the envelope ectodomains [34]. These effects were not seen with a truncation distal to this domain and before LLP1.…”
Section: The Cytoplasmic Tailmentioning
confidence: 93%